Railway infrastructure asset management: the whole-system life cost analysis - Rama, Dovile; Andrews, John D. (Institution of Engineering and Technology, 2016)
Delivering the railway infrastructure whose functionality is sustainable and uncompromised in terms of safety and availability under ever decreasing budget constraints is a great challenge. The successful accomplishment of this task relies on the effective management of individual assets within a wider whole system perspective. This is a highly complex decision-making task where mathematical models are required to enable well-informed choices. In this study, a novel modelling framework is proposed for performing the whole system lifecycle cost analysis. The framework is based on two models: railway network performance and costs. Using the former model investigations of the effects of decisions can be carried out for the individual asset and the whole system. A Petri net modelling technique is used to construct the model. A form of Monte Carlo simulation is then used to obtain model results. The infrastructure performance model is then integrated with the cost model to perform the lifecycle cost analysis. A superstructure example is presented to demonstrate the application of the approach. The results show that taking into account interdependencies among the intervention activities greatly influences, not only the performance of the infrastructure, but also its lifecycle costs and thus should be included in the cost analysis.